Problem-based learning: an exploration of student opinions on its educational role in one UK pharmacy undergraduate curriculum. (13th August 2013) - Wright, David; Wickham, Jane; Sach, Tracey
Abstract: Objective: Problem-based learning (PBL) was introduced into the first 3 years of the undergraduate degree course at the University of East Anglia (UEA) to both enhance the student learning experience and to enable it to meet external course accreditation criteria. Evidence to support both of these assertions is required. The objective was to determine student opinions on the value of PBL and the PBL learning process at one UK school of pharmacy. Method: Utilising the professional accreditation criteria for UK schools of pharmacy a questionnaire was devised and piloted before being given to all UEA undergraduate pharmacy students for self-completion. The most appropriate method of dissemination was determined from a student-led focus group. Key findings: A total of 201/329 (61.1%) students responded. The majority of students agreed that PBL improved their team working (83.1%), oral communication (89.1%) and problem-solving skills (61.7%). Additionally PBL improved students' ability to identify and address ethical dilemmas (74.5%) as well as enhancing their ability to manage their own learning (67.6%). Male students and those with a stated preference for team working were found to prefer PBL. Conclusion: Students generally believe that PBL develops a number of key skills and consequently inclusion of PBL alongside traditional teaching methods enables the school to meet a number of degree accreditation criteria. Male students, those who enjoyed team working and working with their current group were more positive about PBL. Further work is required to improve the experience for all students.